MODEL PEMBELAJARAN KEWIRAUSAHAAN DI PERGURUAN TINGGI - Agustinus Dedy Handrimurtjahjo (Jurnal Universitas Paramadina, 2013)
AbstractEntrepreneurship is a key driver of our economy. Wealth and a high majority of jobs are created by small businesses started by entrepreneurially minded individuals, many of whom go on to create big businesses. Entrepreneurship education in Higher Education is a lifelong learning process, starting from pre-college and progressing through all semesters, until post-graduation. A framework for curriculum development using lifelong learning process that has at least five distinct stages of development: basics, competency awareness, creative application, start-up and growth. This lifelong learning model assumes that everyone in our education system should have opportunities to learn at the beginning stages, while the later stages are targeted at those who may specifically choose to become entrepreneurs. Each of the following five stages may be taught with activities that are infused in other classes or as separate courses.